The Combined Effect of ZnO and CeO2 Nanoparticles on Pisum sativum L.: A Photosynthesis and Nutrients Uptake Study - Elżbieta Skiba (MDPI AG, 2021)
Cerium oxide nanoparticles (CeO2 NPs) and zinc oxide nanoparticles (ZnO NPs) are emerging pollutants that are likely to occur in the contemporary environment. So far, their combined effects on terrestrial plants have not been thoroughly investigated. Obviously, this subject is a challenge for modern ecotoxicology. In this study, Pisum sativum L. plants were exposed to either CeO2 NPs or ZnO NPs alone, or mixtures of these nano-oxides (at two concentrations: 100 and 200 mg/L). The plants were cultivated in hydroponic system for twelve days. The combined effect of NPs was proved by 1D ANOVA augmented by Tukey’s post hoc test at p = 0.95. It affected all major plant growth and photosynthesis parameters. Additionally, HR-CS AAS and ICP-OES were used to determine concentrations of Cu, Mn, Fe, Mg, Ca, K, Zn, and Ce in roots and shoots. Treatment of the pea plants with the NPs, either alone or in combination affected the homeostasis of these metals in the plants. CeO2 NPs stimulated the photosynthesis rate, while ZnO NPs prompted stomatal and biochemical limitations. In the mixed ZnO and CeO2 treatments, the latter effects were decreased by CeO2 NPs. These results indicate that free radicals scavenging properties of CeO2 NPs mitigate the toxicity symptoms induced in the plants by ZnO NPs.